Desarrollo de materiales híbridos nanoestructurados a base de quitina y derivados del grafeno con aplicaciones biotecnológico-ambientales - González, Joaquín Antonio (2018)
The current thesis work is about the development of a chitin based hybrid material loaded with different amount of graphene oxide nanosheets (nGO), a nanoparticle obtained by the chemical exfoliation of graphite. Regarding chitin, it is biopolymer with high chemical resistance and presents poor solubility in most of the common solvents. This apparent drawback would represent an opportunity for the development of new chemical resistant materials once its dispersion is achieved.\nThe synthetized materials were obtained as gels and powder. Both kinds of materials were thoroughly characterized and then applied toward adsorption processes with two mean objectives: the removal of pollutants (environmental focus) and the downstream processing of a protein with commercial interest (biotechnological focus). In the first case, for the environmental purpose the material was used in the gel form, either as pure chitin gel (Chi) and the hybrid gels (Chi:nGO), against pollutant dyes in a batch system. Moreover, the hybrid powder was used in a continuous flow system for the adsorption of ciprofloxacin as an emerging contaminant model. Finally, it was studied the adsorption and desorption of a recombinant peroxidase from an expression medium.